ENHANCING STUDENTS’ TRANSLATION WORKS: A CASE FOR TRANSLATION TEACHING - Ani Gustini; Akhmad Baihaqi (Cakrawala Pedagogik, 2021)
This current study is aiming to investigate the enhancement of students’ translation works of both process and result served by the Student Teams Achievement Division as a learning technique. The study was managed in one private university in Banten Province, Indonesia. Classroom action research was used as a method, and 15 students participated in the study as the subject of the research. The data collecting technique was triangulated by using observation, test, and documentation. The result proves that Student Teams Achievement Division may help students to work cooperatively; they can share and discuss the learning material; then, they can support each other. The results also prove that the average score of pre-cycle is 72 while after Student Teams Achievement Division implementation it improves to 81 in cycle I and 85 in cycle II. Both are categorized as Very Good Translation results. Therefore, it proves that Student Teams Achievement Division can significantly enhance students’ translation works of both process and result, and it can be served as an alternative way in teaching and learning translation.